Research on the path of integrating ideological and political education into technical college teaching - Taking the integration of culture in clothing sewing courses as an example - Yanping , Gu; Rusli , Dr Rose Dahlina (Journal of Islamic, Social, Economics and Development, 2024)
This study aims to explore effective ways of integrating ideological and political education into fashion design courses at technical colleges. The course goal design should emphasize the combination of skill training and ideological and moral education, be specific, operational, and responsive to the needs of the current times and industry. The teaching content should incorporate elements such as traditional culture, social responsibility, and professional ethics in order to deepen and broaden ideological and political education while focusing on cultivating students' independent learning and practical abilities. Teaching methods should prioritize heuristic teaching, diverse practical means, interactive and cooperative teaching methods, as well as personalized and differentiated teaching methods to promote the organic integration of ideological and political education with professional technical education. The evaluation mechanism should scientifically design evaluation indicators, employ diversified evaluation methods, provide timely feedback for continuous improvement aimed at cultivating students' comprehensive quality and innovation ability. This study will offer feasible paths for ideological and political education in technical college teaching while providing theoretical support and practical guidance for nurturing high-quality technical talents with social responsibility and innovation ability.